Creating a Collaborative Practice Environment Which Encourages Sustainable Interprofessional Leadership, Education and Practice : Final Report. - Brewer, Margo; Flavell, Helen; Smith, Megan; Trede, Franziska; Jones, Sue (Office for Learning and Teaching, 2014)
The inadequacy of traditional health services mean that health service models and education practices need to adapt to deliver future health professionals, they will require a different set of capabilities including the capacity to work in interprofessional (IP) teams to deliver client centred care. This is the final report from a project that brought together fieldwork as a means to develop graduate capabilities with the shift to IP practice through designing and implementing a leadership development program for senior health managers and health industry fieldwork coordinators. By building the leadership and change management capacity of those responsible for providing student fieldwork learning environments, the program built capacity for learning and teaching within health practice education and supported national and international drivers for IP practice. A major deliverable of the project for the sector was a leadership development program for IP education and practice (including full resources and facilitator's guide) to create sustainable collaborative practice learning environments.